Dance psychology for artistic and performance excellence - Taylor, Jim 1958- (Human Kinetics, 2015)
Dance Psychology for Artistic and Performance Excellence helps dancers develop psychological strength to maximize their performance. The book covers the key mental aspects of dance performance and offers practical exercises that will make dancers' minds their most powerful tools